Efektivitas Alat Humiditus Berbasis Biomimikri STEAM terhadap Kelembaban dan Potensinya sebagai Alat Peraga IPA SMP - Septia Nabila Fathin; Sulasfiana Alfi Raida (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Room humidity that has long-term adverse effects and the lack of STEAM biomimicry-based science learning aids are the main problems. This study aims to test the effectiveness of the Humiditus tool as a moisture absorber in a closed room and analyze its potential as a STEAM biomimicry-based science teaching aid on the material of living creature adaptation. Humiditus was developed with biomimicry stages that adapt the shape and adaptability of the cactus and the STEAM components in it. The study used a quantitative experimental approach and a descriptive qualitative approach. The sample consisted of two closed rooms that were given different treatments, namely the use of the Humiditus tool and ordinary silica gel. Humidity data were obtained using a hygrometer for three days and analyzed using an independent t-test. The results showed that the Humiditus tool reduced humidity significantly with an average decrease of 22.67% and a significance value of 0.019 (p < 0.05). In addition to being functionally effective, this tool is considered to have strong potential as a science teaching aid because it presents the principle of living creature adaptation in a real and contextual form. Thus, Humiditus not only acts as a technology but also as a teaching aid that supports the learning achievements of the Independent Curriculum on the material on the adaptation of living things.